Functional analysis of a nuclear regulator of circadian clock in fungal development and pathogenesis. - Guo, Jie Ying. (2010)
Magnaporthe oryzae, commonly known as rice blast fungus, is a potent plant pathogen, which infects rice and other cereal crops. The production of asexual spores (conidia), which is induced by light, is important for M. oryzae’s reproduction. In Arabidopsis thaliana, TIME FOR COFFEE (TIC) was found to play an important role in light-sensing. A homolog of TIC was deleted in M. oryzae and the function of Tic was analyzed. The TIC-deletion mutant showed reduced conidiation and pathogenesis. Co-localization of Tic-GFP with histone H1-RFP (hH1-RFP) showed that Tic was localized in the nucleus upon photo-induction. Quantitative real-time PCR (qPCR) showed reduced expression levels of an important feedback component of the Neurospora crassa clock, FRQ in tic∆ compared to the wild type. We suggest that Tic could play an important role in regulation of circadian clock in M. oryzae.